A unique triangle

Geometry Level 3

Triangle Δ A B C \Delta ABC has the following characteristics:

  • (i) its side lengths are three consecutive integers and

  • (ii) its largest interior angle is twice its smallest interior angle.

What is the perimeter of Δ A B C \Delta ABC ?


The answer is 15.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

5 solutions

Let the shortest side length of the triangle be a a . Then the other two side lengths are a + 1 a+1 and a + 2 a+2 . Let the smallest angle be θ \theta ; the largest angle is 2 θ 2\theta . By sine rule , we have:

a sin θ = a + 2 sin 2 θ a sin 2 θ = ( a + 2 ) sin θ 2 a sin θ cos θ = ( a + 2 ) sin θ Since sin θ 0 2 a cos θ = a + 2 cos θ = a + 2 2 a \begin{aligned} \frac a{\sin \theta} & = \frac {a+2}{\sin 2\theta} \\ a\sin 2\theta & = (a+2)\sin \theta \\ 2a\sin \theta \cos \theta & = (a+2)\sin \theta & \small \color{#3D99F6} \text{Since }\sin \theta \ne 0 \\ 2a\cos \theta & = a+2 \\ \implies \cos \theta & = \frac {a+2}{2a} \end{aligned}

By cosine rule ,

a 2 = ( a + 1 ) 2 + ( a + 2 ) 2 2 ( a + 1 ) ( a + 2 ) cos θ Substituting cos θ = a + 2 2 a a 2 = 2 a 2 + 6 a + 5 ( a + 1 ) ( a + 2 ) 2 a Rearranging a 2 + 6 a + 5 = ( a + 1 ) ( a + 2 ) 2 a a ( a + 1 ) ( a + 5 ) = ( a + 1 ) ( a + 2 ) 2 Since ( a + 1 ) 0 a 2 + 5 a = a 2 + 4 a + 4 a = 4 \begin{aligned} a^2 & = (a+1)^2+(a+2)^2 - 2(a+1)(a+2) \color{#3D99F6} \cos \theta & \small \color{#3D99F6} \text{Substituting }\cos \theta = \frac {a+2}{2a} \\ a^2 & = 2a^2 + 6a+5 - \frac {(a+1)(a+2)^2}a & \small \color{#3D99F6} \text{Rearranging} \\ a^2 + 6a + 5 & = \frac {(a+1)(a+2)^2}a \\ a(a+1)(a+5) & = (a+1)(a+2)^2 & \small \color{#3D99F6} \text{Since }(a+1) \ne 0 \\ a^2 + 5a & = a^2 + 4a+4 \\ \implies a & = 4 \end{aligned}

Therefore the perimeter is 4 + 5 + 6 = 15 4+5+6 = \boxed{15} .

Nice solution! Thanks for posting it. :)

Brian Charlesworth - 2 years, 3 months ago

Log in to reply

You are welcome.

Chew-Seong Cheong - 2 years, 3 months ago
Sathvik Acharya
May 11, 2019

Let A C = x 1 , C B = x AC=x-1, CB=x and B A = x + 1 BA=x+1 . Also C = 2 B \angle C=2\angle B as the largest side is opposite to the largest angle and similarly the smallest side is opposite to the smallest angle.

Extend side A C AC to D D such that C D = C B = x CD=CB=x . This implies C D B = C B D = C 2 = B . \angle CDB =\angle CBD = \frac{\angle C}{2}=\angle B. It follows that A B C A D B A B 2 = A C A D ( x + 1 ) 2 = ( x 1 ) ( 2 x 1 ) . \triangle ABC\sim \triangle ADB \implies AB^2=AC\cdot AD\implies (x+1)^2=(x-1)(2x-1).

Simplifying the above equation gives x 2 + 2 x + 1 = 2 x 2 3 x + 1 x 2 = 5 x x = 5 x 1 = 4 , x + 1 = 6 x^2+2x+1=2x^2-3x+1\implies x^2=5x\implies x=5\implies x-1=4, x+1=6 .

Therefore, perimeter of A B C = A B + B C + C A = 6 + 5 + 4 = 15 \triangle ABC=AB+BC+CA=6+5+4=\boxed{15}

Note: There is only one such triangle with these characteristics and it has side lengths of 4,5 and 6.

David Vreken
Mar 12, 2019

Let the sides of the triangle be x 1 x - 1 , x x , and x + 1 x + 1 , and let the smallest angle be θ \theta and the largest angle be 2 θ 2\theta .

By the law of cosines, cos 2 θ = x 2 + ( x 1 ) 2 ( x + 1 ) 2 2 x ( x 1 ) \cos 2\theta = \frac{x^2 + (x - 1)^2 - (x + 1)^2}{2x(x - 1)} which simplifies to cos 2 θ = x 4 2 ( x 1 ) \cos 2\theta = \frac{x - 4}{2(x - 1)} , and cos θ = x 2 + ( x + 1 ) 2 ( x 1 ) 2 2 x ( x + 1 ) \cos \theta = \frac{x^2 + (x + 1)^2 - (x - 1)^2}{2x(x + 1)} which simplifies to cos θ = x + 4 2 ( x + 1 ) \cos \theta = \frac{x + 4}{2(x + 1)} .

Since cos 2 θ = 2 cos 2 θ 1 \cos 2\theta = 2 \cos^2 \theta - 1 , by substitution x 4 2 ( x 1 ) = 2 ( x + 4 2 ( x + 1 ) ) 2 1 \frac{x - 4}{2(x - 1)} = 2 \Big(\frac{x + 4}{2(x + 1)} \Big)^2 - 1 , which solves to x = 5 x = 5 for x > 1 x > 1 .

Therefore, the three integer sides are 4 4 , 5 5 , and 6 6 , for a perimeter of 4 + 5 + 6 = 15 4 + 5 + 6 = \boxed{15} .

K T
Jul 16, 2019

We will use the cosine rule: cos φ = ( a 2 + b 2 c 2 ) / 2 a b \cosφ = (a^2+b^2-c^2)/2ab Apply this to the smallest angle (opposite c, so a and b are the longest sides): a = x + 1 , b = x + 2 , c = x , φ = α a=x+1, b=x+2, c=x, φ=α

cos α = ( x + 1 ) 2 + ( x + 2 ) 2 x 2 2 ( x + 1 ) ( x + 2 ) = x 2 + 6 x + 5 2 x 2 + 6 x + 4 \cos α =\frac{(x+1)^2+(x+2)^2-x^2} {2(x+1)(x+2)} = \frac{x^2+6x+5}{2x^2+6x+4}

Also apply it to the largest angle (opposite c, so a and b are the shortest sides): a = x , b = x + 1 , c = x + 2 , φ = 2 α a=x, b=x+1, c=x+2, φ=2α

cos 2 α = x 2 2 x 3 2 x ( x + 1 ) \cos 2α = \frac{x^2-2x-3}{2x(x+1)}

Now using to the double angle formula cos 2 α = 2 cos 2 α 1 \cos 2α= 2\cos^2α-1 we can relate these values to each other:

x 2 2 x 3 2 x ( x + 1 ) = 2 ( x 2 + 6 x + 5 ) 2 ( 2 x 2 + 6 x + 4 ) 2 1 \frac{x^2-2x-3}{2x(x+1)} = 2\frac{(x^2+6x+5)^2}{(2x^2+6x+4)^2}-1

Working this out eventually leads to the polynomial 2 x 6 + 5 x 5 22 x 4 88 x 3 112 x 2 61 x 12 = 0 2x^6+5x^5-22x^4-88x^3-112x^2-61x-12=0 which can be rewritten as ( x 4 ) ( x + 1 ) 3 ( x + 3 ) ( 2 x + 1 ) = 0 (x-4)(x+1)^3(x+3)(2x+1)=0 with roots x { 3 , 1 , 1 2 , 4 } x \in\{-3,-1,-\frac{1}{2},4\} .

We are looking for a positive integer solution, which is x=4. So the sides are 4, 5, and 6 and the perimeter is 4 + 5 + 6 = 15 4+5+6=\boxed{15} .

Edwin Gray
Apr 2, 2019

Let the triangle sides be n - 1, n, and n + 1. Let B be the angle opposite n - 1 and 2B the angle opposite n + 1. By the Law of Sines: (1) (n - 1)/sin(B) = (n + 1)/sin(2B). (2) 2(n - 1)cos(B) = n + 1 (3) cos(B) = (n + 1)/[2(n - 1)] By the law of cosines, (4) (n - 1)^2 = n^2 + n + 1)^2 - 2n(n + 1)(n + 1)/[2(n - 1)]. Simplifying, (5) n^2 - 5n = 0. So n = 5, n - 1 = 4, n + 1 = 6, perimeter = 15.

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...